Process intensification of anaerobically digested palm oil mill effluent (AAD-POME) treatment using combined chitosan coagulation, hydrogen peroxide (H2O2) and Fenton’s oxidation - Parthasarathy, Shridharan; Gomes, R.L.; Manickam, Sivakumar (Springer Verlag, 2016)
The present study investigates the removal efficiency of chemical oxygen demand (COD) and total suspended solids (TSS) of anaerobically digested palm oil mill effluent in batch studies through the following 4 strategies: coagulation by chitosan, addition of ferrous sulphate (FeSO4), chitosan with hydrogen peroxide (H2O2) and chitosan with Fenton oxidation. The parameters tested were chitosan dosage (500–12,500 mg/L), FeSO4 dosage (500–12,500 mg/L), mixing time (15–60 min), sedimentation time (1–4 h) and initial pH (2–9) and H2O2 (500–7500 mg/L). Coagulation only by using chitosan (2500 mg/L) achieved the maximum COD and TSS removal of 70.22 ± 0.23 and 85.59 ± 0.13 %, respectively. An increase in the TSS removal (98.7 ± 0.06 %) but with a reduction in the COD removal (62.61 ± 2.41 %) was observed when FeSO4 (2500 mg/L) was added along with chitosan (2500 mg/L). Alternatively, an improvement in the COD (82.82 ± 1.71 %) and TSS (89.92 ± 0.48 %) removal efficiencies was observed when chitosan was coupled with H2O2 (500 mg/L). Finally, chitosan (2500 mg/L) integrated with Fenton oxidation (FeSO4 of 2500 mg/L and H2O2 of 500 mg/L) resulted in 100 % TSS and 73.08 ± 4.11 % COD removals. Overall chitosan with H2O2 proved to be the most promising alternative for POME treatment compared to chitosan with Fenton oxidation.